Daya Hambat Ekstrak Biji Durian Lokal Desa Pakis (Durio zibethinus Murr.) terhadap Pertumbuhan Candida albicans - Safira Indah Nafisa (Fakultas Kedokteran Gigi, 2026)
Introduction: Candida albicans is an opportunistic fungus commonly found in the oral cavity that can cause oral candidiasis under conditions of overgrowth. Durian seeds (Durio zibethinus Murr.) are known to contain various bioactive compounds, including alkaloids, phenolics, flavonoids, triterpenoids, and lectins, which exhibit antifungal properties. This study aimed to evaluate the inhibitory effect of durian seed extract from Pakis Village on the growth of Candida albicans. Methods: This laboratory experimental study employed the disk diffusion method. The samples were divided into six groups (n = 5 per group): a negative control (sterile distilled water), durian seed extract at concentrations of 12.5%, 25%, 50%, and 100%, and a positive control (nystatin). The inhibition zones were measured using a caliper. Data were analyzed using the Kruskal-Wallis test, followed by the Mann-Whitney post hoc test. Results: The 12.5% and 25% concentrations showed no inhibitory activity, whereas the 50% and 100% concentrations produced mean inhibition zones of 6.62 ± 0.23 mm and 10.12 ± 0.96 mm, respectively. The nystatin group exhibited the largest inhibition zone (18.28 ± 0.61 mm). Statistical analysis revealed significant differences among the treatment groups (p<0.05). Conclusion: Durian seed extract from Pakis Village at concentrations of 50% and 100% inhibits the growth of Candida albicans, with greater efficacy observed at higher concentrations.
FINALISASI oleh Arif 2026 Juni 22
Keywords: Candida albicans; antifungal activity